Survey on Mission Planning of Multiple Unmanned Aerial Vehicles - Song, Jia; Zhao, Kai; Liu, Yang (Aerospace, 2023)
The task assignment issue and the path planning problem of Multiple Unmanned Aerial Vehicles (Multi-UAV) are collectively referred to as the Mission Planning Problem (MPP). This review article provides an update on the progress of the MPP on Multi-UAV. Focusing on the burning issue of task assignment, this paper focuses on the comparison of the characteristics of the mathematical programming method, heuristic algorithm, negotiation algorithm and neural networks. According to different constraints, trajectory planning can be divided into 2 dimension coverage, 3 dimension cooperation, and 4 dimension space-time cooperation. Combined with typical research, common collaborative guidance methods are introduced, and the key development direction of this field is prospected. The article shows that, although the MPP has been extensively studied, ongoing research is required. In particular, it is necessary to pay attention to the timeliness of the task assignment, the information coupling exists in MPP, and the problems caused by multiple constraints of Multi-UAV and environmental uncertainty.